Piezoelectric properties of [001]-textured high-power PMnN-PZT piezoceramics sintered at a low temperature. Issue 5 (May 2023) - Kim, Eun-Ji; Kim, Sun-Woo; Kim, Dae-Su; Go, Su-Hwan; Chae, Seok-June; Eum, Jae-Min; Yu, Hyeon-Min; Chae, Yeon-Gyeong; Nahm, Sahn
Abstract: The 1.0 mol% CuO-added 0.14Pb(Mn1/3Nb2/3)O3 -0.86Pb(Zr0.55 Ti0.45 )O3 (CPMnN-PZT) piezoceramics were synthesized at low temperatures (≤ 950 °C) by the columbite method to remove the pyrochlore phase. It exhibited a high Q m of 3016 and a high T C of 309 °C. However, it showed small d 33 and k p values of 143 pC/N and 0.43, respectively. The CPMnN-PZT piezoceramic was textured along the [001] direction using BaTiO3 (BT) templates to enhance its soft piezoelectric properties. The [001]-textured CPMnN-PZT + y vol% BT piezoceramics (1.0 ≤ y ≤ 5.0) were densified at a low temperature of 950 °C with a high Lotgering factor (≥ 92%). The textured sample (y = 1.0) showed a high Q m of 1400 with increased d 33 and k p values of 278 pC/N and 0.58, respectively, and its piezoelectricity showed excellent temperature stability up to 225 °C. Therefore, the textured CPMnN-PZT sample can be used for developing high-power piezoelectric devices. Highlights: PMnN-PZT thick films were textured along the < 001 > direction using BT templates. [001]-textured PMnN-PZT thick films were sintered at 950 °C using CuO additive. Textured PMnN-PZT thick film showed large Q m (1400), d 33 (280 pC/N) and k p (0.58). Textured PMnN-PZT thick film maintained piezoelectric properties up to 225 °C.